Design, synthesis and in vitro evaluation of benzothiazole-based ureas as potential ABAD/17β-HSD10 modulators for Alzheimer's disease treatment - Hroch, Lukas; Benek, Ondrej; Guest, Patrick; Aitken, Laura; Soukup, Ondrej; Janockova, Jana; Musil, Karel; Dohnal, Vlastimil; Dolezal, Rafael; Kuca, Kamil; Smith, Terry K; Gunn-Moore, Frank; et al. (Bioorganic & medicinal chemistry letters, 2016)
Amyloid-beta peptide (Aβ) has been recognized to interact with numerous proteins, which may lead to pathological changes in cell metabolism of Alzheimer's disease (AD) patients. One such known metabolic enzyme is mitochondrial amyloid-binding alcohol dehydrogenase (ABAD), also known as 17β-hydroxysteroid dehydrogenase type 10 (17β-HSD10). Altered enzyme function caused by the Aβ-ABAD interaction, was previously shown to cause mitochondrial distress and a consequent cytotoxic effect, therefore providing a feasible target in AD drug development. Based on previous frentizole derivatives studies, we report two novel series of benzothiazolyl ureas along with novel insights into the structure and activity relationships for inhibition of ABAD. Two compounds (37, 39) were identified as potent ABAD inhibitors, where compound 39 exhibited comparable cytotoxicity with the frentizole standard; however, one-fold higher cytotoxicity than the parent riluzole standard. The calculated and experimental physical chemical properties of the most potent compounds showed promising features for blood-brain barrier penetration.
Keywords: CHO buňky; vztahy mezi strukturou a aktivitou; Humans; Structure-Activity Relationship; Molecular Structure; zvířata; Cricetulus; Benzothiazoles; Alzheimerova nemoc; Drug Design; močovina; Alzheimer Disease; benzothiazoly; inhibitory enzymů; Cell Survival; viabilita buněk; 3-hydroxyacyl-CoA-dehydrogenasy; CHO Cells; Dose-Response Relationship, Drug; Animals; vztah mezi dávkou a účinkem léčiva; lidé; Urea; racionální návrh léčiv; Enzyme Inhibitors; 3-Hydroxyacyl CoA Dehydrogenases; molekulární struktura